Gaucher's disease diagnosed by splenectomy - Adas, Mine (Medknow Publications & Media Pvt Ltd, 2009)
CONTEXT: Splenectomy continues to find common therapeutic indications for hematologic disorders. In addition, recently it is also performed in surgical clinics to assist diagnose of some illnesses. Gaucher's disease, especially Type I, is the most frequently encountered lysosomal storage disorder in man. Manifestations of it are highly variable. The most frequently found symptoms include splenomegaly with anaemia and thrombocytopenia, mostly due to hypersplenism, hepatomegaly and bone disease. CASES: Four patients were reported in the present study. Three of them were easily diagnosed with Gaucher's disease via bone marrow cytology, and one with Gaucher's disease was detected by pathological examination following the splenectomy. CONCLUSIONS: For the pouse of diagnosis of the Gaucher's disease, performing surgery is generally not necessary. However, for the cases of difficult to diagnose by classical methods, the corect diagnosis of Gaucher's disease can only be made by a special operation.